Beyond Immediate Needs: An Analysis of Social Insurance and Its Behavioral Economic Impact in Indonesia - Palupi, Ucca Bhanuwati Astutiningtyas (BPJS Kesehatan, 2024)
Despite the relatively high GDP growth of around 5.3 in 2022, Indonesia still faces high inequality (Gini index 37.9), which challenges social-economic-security instruments. In January 2023, the government spent around IDR 5.3 trillion to protect public health, a 12% increase compared to last year (2022), making Badan Penyelenggara Jaminan Sosial Kesehatan shortened by BPJS Kesehatan as a medic-aid social insurance manager need to keep evolving to suffice the need. In this research, we investigate the potential impact of social insurance in Indonesia to determine the possible direction of the relationship between the adequacy of social-economic-security instruments and spending. The study utilises a vector error correction model (VECM) test as a tool to analyse quarter data from several online source datasets, including household consumption expenditures, gross national income, and capital stock from bps.go.id, social insurance participations from djsn.go.id, inflation and national savings proxy by broad money M2 from bi.go.id in the form of quarterly data, starts from 2016 Q1 until 2023 Q3. The regression result shows no immediate and significant relationship between social insurance and consumption. However, the analysis reveals that social insurance might contribute to economic resilience, potentially leading to higher productive spending and a potential behavioural transformation towards risk.